1999
DOI: 10.1046/j.1365-2648.1999.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and perceived nurse caring in nurse–patient dyads

Abstract: The effect of nurse gender on nurse and patient perceptions of nurse caring was explored. Members of nurse-patient dyads (N = 145), equally distributed among the four possible gender combinations, completed matching forms of the Caring Questionnaire immediately following a shift. Perceptions of nurse caring that actually occurred during the preceding shift, as well as usual preferences about nurse caring, were measured. Results of two-factor ANOVAS showed no significant differences in actual caring according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 22 publications
0
49
2
2
Order By: Relevance
“…Larsson et al (1998) highlighted the need for further investigation of what makes patient-staff communication effective on the grounds that it may contribute to more effective staff assessment of patient perceptions. Ekstrom (1999) found a significant gender effect amongst nurses and argued for future investigations into the impact of gender on perceptions of nurse caring. Gardner et al (2001) suggested that future research needed to consider potential differences in the perceptions of 'junior' and 'senior', 'younger' and 'older' nurses and 'Enrolled and Registered nurses.…”
Section: Research Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Larsson et al (1998) highlighted the need for further investigation of what makes patient-staff communication effective on the grounds that it may contribute to more effective staff assessment of patient perceptions. Ekstrom (1999) found a significant gender effect amongst nurses and argued for future investigations into the impact of gender on perceptions of nurse caring. Gardner et al (2001) suggested that future research needed to consider potential differences in the perceptions of 'junior' and 'senior', 'younger' and 'older' nurses and 'Enrolled and Registered nurses.…”
Section: Research Issuesmentioning
confidence: 99%
“…They noted the limitation of relying upon staff perception about a hypothetical or average patient and suggested the study of more closely aligned samples of matched patient-nurse dyads where patients answered for themselves and staff responded in relation to specific patients in their care. Research proceeded then to focus specifically upon matched dyads in cancer care (von Essen et al 1994(von Essen et al , 1995, nursing home care (Smith and Sullivan 1997) and acute care (Ekstrom 1999). Larsson et al (1998) utilised a larger sample of matched dyads in cancer care in an effort to increase the representativeness of their findings.…”
Section: Development Of Effective Samplingmentioning
confidence: 99%
“…Such a perception may be due to the gender-biased view that men are good at handling machines and possess better problem-solving skills (Kleinman, 2004). However, male nurses are thought to be less sensitive to other people's emotions and less caring than female nurses (Ekstrom, 1999;Hodes Research, 2005). Last, the sexual orientation of male nurses has often been questioned by the public, and many male nurses are unfairly assumed to be homosexual and effeminate (Fisher, 2009;Hodes Research, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…People tend to believe that male nurses have different attributes than female nurses in terms of leadership qualities, masculinity, technical ability, sensitivity to the emotions of others, and the impact of their sexuality (Anthony, 2004;Ekstrom, 1999;Fisher, 2009;Hodes Research, 2005;Keogh & O'Lynn, 2007;Kleinman, 2004). Male nurses have been perceived as better at taking up leadership roles than female nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Mannlege sjukepleiarar uttrykkjer seg på ein annan måte enn kvinner om kva omsorg er, men dei gjer det ikkje i utførering av omsorg. Pasientane meinte at kjønn hjå sjukepleiarane hadde innverknad på korleis omsorg vart utført (10). Lutzen og Nordin (11) sine studie i Sverige ved hjelp av The Moral Sensitive Questionnaire viser at kjønn, erfaring og utdanning er alle faktorar som innverkar på å ta moralske avgjersler i utøving av psykiatrisk sjukepleie (11).…”
unclassified